Review Creativity Department of Education Staff and Its Relation to Quality of Work Life - Ghasemi, Mohammad; Ganji, Mohammad Reza; Fotohi, Mehdi; Nik, Mosa Faghihi; Solor, Rohoallah Ghofran (International Review of Management and Marketing, 2017)
Quality of work life is an approach that seeks to improve the quality of life of working people and tries to respond job needs that declines to the production role alongside other factors such as capital and is resulted to alienation. The purpose of this article is to review Creativity Department of Education staff and its relation to quality of work life. This study is an applied, descriptive and correlational research in terms of purpose, nature and methods. The study's statistical population consisted of all employees of Department of Education of zabol in 2017 who were over 300 people. To determine sample size, 169 people were chosen using Cochran formula. In this study, inferential statistics such as Spearman correlation coefficient was used for data analysis. The results showed that there is a relatively strong and positive relationship between quality of working life and staff Creativity (R = 0.558). Also, there is a positive relationship between the overall atmosphere of the components of life, providing opportunities for growth, safe and healthy working environment, and social dependence of working life, legalism, development of individual capabilities, fair pay and solidarity and social cohesion with employee Creativity with correlation coefficient, 0.635, 0.579, 0.586, 0.469, 0.456, 0.452, 0.399 and 0.397, respectively. Keywords: quality of life, Creativity, staff, Department of Education of zabol JEL Classifications: C32; O13; O47